Vaccinia virus morphogenesis is interrupted when expression of the gene encoding an 11-kilodalton phosphorylated protein is prevented by the Escherichia coli lac repressor. - Zhang, Y F (J Virol, 1991)
A conditional lethal vaccinia virus mutant, which constitutively expresses the Escherichia coli lac repressor and has the lac operator controlling the F18R gene (the 18th open reading frame of the HindIII F fragment of the vaccinia virus strain WR genome) encoding an 11-kDa protein, was previously shown to be dependent on the inducer isopropyl-beta-D-thiogalactoside (IPTG) for replication (Y. Zhang and B. Moss, Proc. Natl. Acad. Sci. USA 88:1511-1515, 1991). Further studies indicated that the yield of infectious virus could be regulated by titration with IPTG and that virus production was arrested by IPTG removal at appropriate times. Under nonpermissive conditions, an 11-kDa protein reactive with antiserum raised to a previously described DNA-binding phosphoprotein (S. Y. Kao and W. R. Bauer, Virology 159:399-407, 1987) was not synthesized, indicating that the latter is the product of the F18R gene. In the absence of IPTG, replication of viral DNA and the subsequent resolution of concatemeric DNA molecules appeared normal. Omission of IPTG did not alter the kinetics of early and late viral protein synthesis, although the absence of the 11-kDa polypeptide was noted by labeling infected cells with [35S]methionine or [32P]phosphate. Pulse-chase experiments revealed that proteolytic processing of the major viral structural proteins, P4a and P4b, was inhibited under nonpermissive conditions, suggesting a block in virus maturation. Without addition of IPTG, the failure of virus particle formation was indicated by sucrose gradient centrifugation of infected cell lysates and by the absence of vaccinia virus-mediated pH-dependent cell fusion. Electron microscopic examination of infected cells revealed that immature virus particles, with aberrant internal structures, accumulated when synthesis of the 11-kDa DNA-binding protein was prevented. IMAGES: